O racjonalności religii w uwikłaniu - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2010)
Zbigniew Drozdowicz – ON RATIONALITY OF RELIGION IN ENTANGLEMENT In my considerations I will make an attempt to deliver an answer to the question of rationali-ty of religion, which is related to social action and is being entangled in social relations of various kinds. In this point of view I’m inspired by the approach in this matter of Max Weber, and mod-ern weberians like Peter L. Berger and Thomas Luckmann. The picture of rationality emerging from the considerations of these scholars is, and cannot be, unequivocal, but is at least clear enough to recognize, describe, and explain these rations without which we cannot speak of any rationality. The most ge-neral formula for this rationality is Leibnitz’s quotation: “Nothing is without a right argument” or (which is basically the same) “Everything has its own right argument” filled with Weber’s quotation “A social argument has everything which is people oriented” Berger and Luck-mann add to it “(...) at other significant people”.